Politicisation and Democracy: The Consequences of Contingency - Claudia Wiesner (Politics and Governance)
The article develops the relation of politicisation and democracy theoretically, normatively, and conceptually. Politicisation is defined as marking something as collectively relevant and as an object of politics, and hence as debatable or contested. Democracy, and concretely liberal or representative democracy, means organised self‐government of the citizens via elected representants. It is marked by a set of institutions and rights based on the rule of law on the one hand, and by political action and (regulated) controversies and processes of collective decision‐making on the other. How do the two relate to one another? The article proceeds as follows. First, I conceptualise politicisation and its linkages to the concept of politics. Two ideal‐typical conceptions of politics are developed, i.e., (a) a spatial understanding of politics as a system, area, field, or sphere, and (b) an understanding of politics as action. The following reflections are based on an action‐oriented understanding of politics and politicisation, arguing that politics consists of political action(s) and politicisation is the act of marking an issue as political. Therefore, both politics and politicisation potentially can take place anywhere and anytime, inside and outside of the classical political system. The third section discusses conceptually and theoretically whether and to what extent politicisation is compatible with liberal representative democracy: if politicisation is action, then it can be both democratic and anti‐democratic action, and the ensuing question is how liberal representative democracies react to this challenge. On this basis, the grey zones around populism, polarisation, and democratic backsliding are discussed, in order to further clarify existing and possible current interrelations between politicisation and liberal representative democracy. The article concludes with a typology of four types of interrelations between politicisation and democracy.